STANDARDIZATION OF JAMBAVASAVA - A POLYHERBAL AYURVEDIC FORMULATION - Shyamkant, Chumbhale Deshraj; J, Chavan M; D, Upasani C (Asian Journal of Pharmaceutical Research and Development, 2018)
Standardization of herbal formulation is an essential tool for assessment of quality of drugs based on physical properties and chemical content. The present paper reports on standardization of procured sample of marketed Jambavasava prescribed for the treatment of diabetes. Present study was includes various physico-chemical standards such as pH, specific gravity, viscosity, acid value, total solid, total alcohol, reducing sugar and non-reducing sugar, heavy metal and mineral content. Quantitative chemical estimation of total phenolic content was done by Folin- Ciocalteu reagent method using gallic acid as a standard. Also major heavy metals and minerals content was determined by Atomic absorption spectrometer (ASS).The pH, specific gravity, viscosity, acid value, total solid, total alcohol, reducing sugar and non-reducing sugar was found to be 3.87 ± 0.010, 1.23 ± 0.006, 1.663 ± 0.011 cp, 0.08 ± 0.004, 33.67 ± 0.005 % w/v, 7.86 ± 0.015 % v/v, 8.03 ± 0.058 % w/v and 0.25 ± 0.030 % w/v respectively. Phenolic content of Jambavasava by Folin- Ciocalteu reagent method by comparing with gallic acid as a standard was found to be 0.062 ± 0.001 % w/v. Estimated heavy metals and minerals of Jambavasava showed presence of heavy metals such as Lead 4.96 ppm, Aluminum 182 ppm and minerals includes Zinc 26.90 ppm, Copper 11.6 ppm, Irons 158 ppm, Nickel 3.59 ppm and Chromium 0.29 ppm indicated within a safety limit. Present study has to compile the quality control standards of polyherbal Jambavasava for the authenticity of drug sample and its pharmacopoeial monograph information for the better and safe use in the therapeutics.